(untitled) (Bulletin KNOB, 1996)
There were strong ties between Adriaen Dortsman and Jan Six. This is not only evident from the private house that Six was having built from 1667-1669, but also from the court-house and the country house at Wimmenum. Six’s interest in architecture does not just appear from the commissions, but also from his intervention in the town hall of Amsterdam at the time, the books he possessed and the sketch he made of the country house at Wimmenum. From the drawings that have been preserved of a preliminary design of the Six house dating from 1666 much information can be gathered on the layout and furnishing of a house such as Dortsman initially planned it. Dortsman’s innovative exteriors appear not to have led to any modernization of the interiors. The layout of the Six house was guided by the traditions and customs in building at that time; notably a link seems to have been sought with the just completed and very prestigious Trippenhuis (1662) after a design by Justus Vingboons. Among other things this is apparent from the ground plan of the first floor and from the use of an alcove. In the details of the elements of the interior, too, Dortsman keeps within the tradition of his time: if possible he applies fashionable elements. The comparison between the interior of the Six house and other interiors by Dortsman shows particular preferences: the use of a round, closed niche around or above a door in the vestibule or hall, followed by a circular niche, the fireplace with shored up side-pieces and if possible an alcove. The alcove in Gunterstein may well be regarded as the most monumental one of its kind. These fixed elements also recur in the dolls’ houses of Sara Rothé, which contain interiors from dolls’ houses of Cornelia van der Gon, Dortsman’s housekeeper. It is more than likely that parts of these were designed by Dortsman, which fact is an important new source for Dortsman interiors dating from approximately 1680. In the later and more lavishly executed interior designs Dortsman tries to create entire environments instead of just components of them. In the Six house and the Walenweeshuis (orphanage) only the fireplaces are in accordance with a design by Dortsman, in which only the centres were left unornamented, whereas the later works, such as Gunterstein and two interiors of the dolls’ house in The Hague show a more encompassing interior image. The centre is involved in the design of the fireplace, apart from the fact that entire walls were designed by Dortsman, as appears from the walls of the alcove and kitchen in the dolls’ houses.